Investigating Smart Parcel Locker System s in the Framework of Planned Behavior Theory: A Study of Electronic Last Mile Delivery Processes on E-Commerce Platforms - Yavuz Toraman (Journal of Transportation and Logistics)
As digitalization touches human life at many different points, consumers’ perceptions toward innovations have been a matter of curiosity for experts. In this context, examining the factors affecting consumer acceptance of new technologies constitute the main problem of the research. The study uses planned behavior theory (PBT), which is suitable for the purpose of the research and has been frequently mentioned in the literature. The study also uses structural equation modeling due to the presence of more than one relationship in the PBT model. The study uses the program SmartPLS 3, which has also been frequently used for structural equation modeling in the literature. The results from the reliability and validity analyses of the study data were found to be within accepted values, and thus the SmartPLS 3 path analysis was conducted. The study accepted all its hypotheses except for the H4. Perceived behavioral control (PBC) variable could not provide reliable data regarding the additional questions included in the study because less than 30% of the participants used locker technology. Because a sufficient number of smart parcel locker users could not be reached and the obtained R² value was 0.122, the research focused on explaining user intent rather than behavior. The fact that PBC affects both intention and behavior indirectly reveal a result to have been obtained that is parallel to the literature. However, with the accelerated use of technology and the spread of parcel lockers to a wider area, the rate of smart parcel locker technology usage in last mile delivery will increase. By benefitting from technology, this study predicts that the last mile delivery process with parcel lockers will be called electronic last mile delivery.